Independent State, Federal State, or Unitary State? Age, Gender, and Regional Differences Among Anglophone Cameroonians - Elvis Nshom (Social Sciences)
For the past 8 years, Cameroon has been witnessing a deadly conflict between anglophone separatist fighters and the Cameroon military over the form of governance. This study seeks to highlight anglophone attitudes and preferences towards forms of governance, as well as the differences between men and women and between northwesterners and southwesterners, i.e., the inhabitants of the two English-speaking regions in Cameroon, with respect to this question. In addition, it explores the relationship between age and attitudes toward the form of state. In a sample of 314 participants, the results show that men were more supportive of an independent state than women, but women were more supportive of a federal state than men. On the other hand, support for a unitary state, the current form of state, was extremely low, and there was no significant difference between men and women. Also, this study shows that there is no significant difference between anglophones from the northwest region and anglophones from the southwest region in terms of their support for an independent state, a federal state, and a unitary state. Lastly, the results indicate that there is a significant positive correlation between age and support for an independent state, a significant negative correlation between age and support for a federal state, and a nonsignificant negative correlation between age and support for a unitary state. The implications, limitations, and recommendations of this study are discussed as well.